Dynamic architecture Heliotrope. Freiburg, Germany - Gutiérrez Ortegano, Antonio (2022)
Along the history the technology has allowed significant advances in the architecture, giving origin to new trends, styles and representative works. In the architectural conception, innovation and technology they go of the hand, which generates results that they change and evolve across the time, depending on the historical, cultural, social and economic context in which they are. In the present investigation one will refer to the dynamic architecture, where a representative work will define and exemplify, Heliotrope, who will allow to visualize and to understand the concepts and offers that this architectural trend raises.